Surgical treatment of dementia associated with hydrocephalus - Jerí, F. Raúl (1969)
Two cases of communicating hydrocephalus with normal cerebro-spinal fluid pressure are reported. Both patients were referred because of mental deficiency associated with severe behaviour disturbances. The ventriculo-atrial shunt, using the low pressure Pudenz-Heyer valve, modified considerably the behaviour disorders and the intellectual quotient in both patients.